High temperature and solar radiation in the Red Sea enhance the dissolution of crude oil from surface films - Sreejith Kottuparambil; Ananya Ashok; Patricia López; Maan H. Amad; Carlos M. Duarte; Susana Agusti (Environmental Science and Pollution Research, 2024)
The Red Sea is a hotspot of biodiversity susceptible to oil pollution. Besides, it is one of the warmest seas on the Earth with highly transparent waters. In this study, we estimated the oil dissolution rates under natural sunlight spectra and temperature conditions using coastal oil slicks collected after the 2019 Sabiti oil spill in the Red Sea. Optical analyses revealed the significant interactive effect of sunlight and temperature in enhancing the dissolution of oil into dissolved organic matter (DOM). The highest oil dissolution rate (38.68 g C m −3 d −1 ) was observed in full-spectrum sunlight. Oil dissolution significantly enhanced total organic carbon (TOC) and polycyclic aromatic hydrocarbons (PAHs) in seawater. High nucleic acid (HNA) bacteria, likely the oil degraders, proliferated from 30 to 70 – 90% after 4 days. The heavier stable carbon isotopic composition of methane (δ 13 C-CH 4 ) and lighter stable carbon isotopic composition of carbon dioxide (δ 13 C-CO 2 ) indicate the putative role of bacterial processes in the natural degradation of crude oil. The results indicated that the combined effect of temperature and solar radiation enhanced the biological and photochemical dissolution of oil on the Red Sea surface.